DECISION MAKING FOR PROJECT SELECTION IN PT. JKT WITH ANALYTIC HIERARCHY PROCESS (AHP) METHOD - R. Daffa Andaru Fawwaz Naufal; Pri Hermawan (CV. Radja Publika, 2025)
The focus of this study is how PT. Jawara Kanistha Tibra (JKT) makes decisions about three projects: